Tufalin Demir Cevheri Konsantresi İle Karıştırılarak Pelet Üretiminde Kullanılabilirliğinin Ve İndirgenebilirliğinin İncelenmesi - Işıkgül, Osman (Fen Bilimleri Enstitüsü, 2012)
Ülkemizde çelik üretiminin % 74’ü elektrikli ark fırınları ile gerçekleşmektedir. Elektrikli ark ocaklı tesislilerin üretim yapabilmeleri için gerekli olan hurda genel olarak ithalat yoluyla sağlanmaktadır. Hurda da oluşan dışa bağımlılığı giderebilmek için yerli kaynakların kullanılması ve hurdaya alternatif ürün elde edilmesi gerekliliği ortaya çıkmaktadır. Doğrudan indirgenmiş demir, demirli hammaddelerin katı veya gaz redükleyici kullanılarak ergime olmaksızın, indirgenmesi sonucunda ortaya çıkan bir üründür. Yüksek metalizasyon derecesine sahip bu ürün, kararlı bileşime sahip olması ve bünyesinde iz elementini az bulundurması nedeniyle, elektrikli ark fırın tesislerinde hurdanın yerine alternatif olarak ve bazik oksijen fırınlarında şarj malzemesi olarak kullanılmaktadır. Tufal, haddehanelerde, sürekli döküm tesislerinde, tav fırınlarından çıkan çelik, slab ve kütük yüzeylerinde tavlama esnasında gerçekleşen oksitlenme sonucu oluşan demir oksit tabakasıdır. Yaklaşık olarak % 70 oranın demir içeren bu madde uzun yıllardır demir – çelik tesislerinde atık olarak düşünülüp satılmıştır. Son yıllarda ülkemizde tufalden, kurulan tesislerle doğrudan indirgenmiş demir üretimi yapılıp, demir çelik sektörüne tufalin geri dönüşümü sağlanmaya başlanmıştır. Bu maddenin geri kazanımı, hem ekonomik olarak hem de çevresel açıdan kazanç sağlayacaktır. Bu çalışmada, tufalin çok ince boyutlara öğütülmeden, manyetit cevheri konsantresi ile karıştırılarak pelet üretiminde kullanılabilirliğinin belirlenmesi ve yine tufalin çok ince boyutlara öğütmeden manyetit cevheri, indirgeyici olarak soma-linyit kömürü ve bentonit ile briketlenerek indirgenebilirliğinin saptanması amaçlanmıştır. Çalışma kapsamında pelet üretimi deneyleri laboratuar tipi peletleme diskinde, indirgeme deneyleri ise elektrik dirençli fırında gerçekleştirilmiştir. Deneylerde, karışımlardaki artan tufal miktarının ( % 40, 50, 60 ve 70) pelet üretimine ve metalizasyona etkisi incelenmiş, indirgeme deneylerinde artan süre de bir parametre olarak belirlenmiştir. Çalışmada kullanılan tufal enerji verimliliği açısından çok ince boyutlara öğütmeden -1 mm boyutuna indirilerek kullanılmış olup, manyetit cevheri konsantresi ise peletleme boyutunda kullanılmıştır. Deneyler sırasında alınan numunelerin analizlerinden elde edilen veriler değerlendirilerek artan tufal miktarının peletleme ve indirgeme reaksiyonu üzerindeki etkisinin belirlenmesi amaçlanmıştır. Yapılan deneyler ve analizler sonucunda elde edilen verilerin incelenmesiyle, karışımlardaki artan -1 mm boyutundaki tufal miktarının uygun pelet üretimini olumsuz yönde etkilediği, peletleme deneylerinde gerek pelet boyutu gerekse basma mukavemet değerleri açısından en iyi ve yeterli sonuçların % 40 tufal -% 60 manyetit cevheri konsantresi karışımıyla elde edilen peletlerde sağlandığı, pelet boyutunun 9-15 mm arasında, pişirme sonrası basma mukavemet değeri ise 210 kg/pelet olduğu belirlenmiştir. İndirgeme deneylerinde ise, % 40, 50, 60 ve 70 tufal içeren karışımlara indirgeyici olarak ilave edilen soma-linyit kömürü ile elde edilen briketlerin indirgenmesi sonucunda en yüksek metalizasyon oranları sırasıyla, % 92.02, 77.75, 82.11ve 87.97 olarak belirlenmiştir. En yüksek metalizasyon oranı % 40 tufal+%60 manyetit cevheri konsantresi+stokiometrinin 1.5 katı karbon sağlayacak soma-linyit kömürü+%1 bentonit karışımıyla elde edilen briketlerin indirgenmesi ile 60. dakika sonunda % 92.02 mertebesinde belirlenmiştir. İndirgeme deneylerinde endüstriyel olarak kullanılabilecek doğrudan indirgenmiş demir için tufalin çok ince boyutlara öğütülmeden kullanılabileceği ve artan tufal miktarının metalizasyon oranı üzerine kayda değer bir etkisinin olmadığı tespit edilmiştir.

Steelmaking has been around since ancient and medieval times, when steel was produced by heating and manipulating iron ore at temperatures below the melting point of iron, and then going through the laborious ritual of re-heating and manual reworking to eventually end up with a useable piece of steel. Nowadays, steel production takes place in two different ways. The first production way is performed by using iron ore and coke at integrated iron and steel plants. The other production way is performed by using scrap or alternative (direct reduced iron) materials at EAF facilities. Iron and steel industry tends EAF facilities due to high investment costs, energy requirements and environmental factors of integrated iron steel plants. EAF facilities have various property as low investment cost, work at small scale etc. In terms of production processes 74% of the total steel production of Turkey is realized by electric arc furnaces. It is necessary to make the production of electric arc furnaces in general is provided through import of scrap. Use of domestic resources and produce the alternative product to scrap is provide to solve scrap import dependence. Direct reduction iron is the product obtained through reduction of ferrous raw materials by gaseous or solid reductants, without any melting of the feed. Direct reduced iron is alternatively used instead of scrap in electric arc furnace and basic oxygen because of the characteristic properties which is high metallization degree, low impurity content and stability in composition. Substantial developments in direct reduction ironmaking (DRI) technologies have been recently conducted providing sustainable mean, for metallurgical operations. The largest advantage of the DRI technologies relies on the fact that DRI does not require cokemaking and sintering. Both cokemaking and sintering, being at the front end of the conventional blast furnace ironmaking technology, are considered as costly for the new process construction and are consistently causing environmental concerns. The DRI process, on the other hand, consists of carbothermic reduction of iron oxide directly with the volatiles liberated during coal devolatilisation as well as the carbon monoxide regenerated from coal char. This process provides an advanced utilisation opportunity for the high volatile coals, which were otherwise unusable in the steel industry. In recent years, the demand for direct reduced iron has been increasing. This increase is due to the growing steel production in EAF facilities. EAF facilities seek the products that require low impurity raw materials contributes to increasing demand. The increasing total steel production led to difficulties in supplying ferrous raw materials for EAF facilities. Lack of supplying ferrous raw materials facilities can be solved by direct reduced iron. Mill scale is an oxidized layer of steel alloys containing iron oxide on the surface of slabs and billets occurring during annealing in heating furnace at integrated iron and steel milling plant and continuous casting unit. This material which contains both iron in elemental form and three types of iron oxides: wustite (FeO), hematite (α-Fe2O3) and magnetite (Fe3O4). The iron content is normally around 70 %, with traces of non-ferrous metals and alkaline compounds, was sold as waste for many years by iron-steel facilities. Mill scale is contaminated with remains of lubricants and other oils and greases from the equipment associated with rolling operations. The oil content usually ranges between 0.1 and 2.0 %, but can reach up to 10.0 %. Mill scale is formed by flaky particles of a size of generally less than 5.0 mm. The size distribution depends on the point in the process where the mill scale is generated. The smallest particles (< 0.1 mm), known as mill scale sludge, are normally collected in the process water treatment units located close to the rolling machines. Recycling of mill scale will have economical and environmental benefits. The reduction of mill scale to sponge iron (direct reduced iron) powder is a new way to take advantage of a cheap by-product of the steelmaking industry, yielding sponge iron that can be re-used to the electric furnace as metallic charge for steelmaking to obtain a product with a lower residual content and improved properties. In this study determining usability of mixing mill scale, which is ungrinded fine sizes, with magnetite ore concentrate for pellet production and reducibility of briquetting mill scale with mixed magnetite ore concentrate, Soma-lignite coal and bentonite, is aimed. Scrobe of this study, all experiments were made on pelletizing disc which is using for testing of pellet production and electric resistance furnace which is using for reduction. The effect of increasing mill scale quantity in the mixing on production of pellet and metallization was inspected in these experiment. Mill scale, ungrinded fine size, which has -1mm, was used for energy efficiency.and magnetite ore concentrate that was used for experiments, has pelletizing size. Evaluation of the data collected by the analyses of the specimens acquired during the experiments intent to determine the effect of increasing mill scale quantity in the mixing on pelletizing and reduction reaction. Examination of the data obtained in the experiments and analyzes, -1 mm in size in the mixtures increased the amount of oxide layer was found to negatively affect the production of appropriate pellets. Pellet size and the compressive strength values of pelletizing experiments in terms of both good and satisfactory results in the pellet that was obtained by % 40 mill scale- % 60 magnetite ore concentrate mixture. Pellets which are prepared by % 40 mill scale- % 60 magnetite ore concentrate mixture were reached the size of 9-15 mm and achieved the compressive strength of 210 kg/pellet. In the reduction experiments, it was occurred that % 40, 50, 60 and 70 mill scaled mixtures were added soma-lignite coal in a reductant way and the whole is briquetted. After the whole briquettes are reduced, the highest metallization rates were analyzed % 92.02, 77.75, 82.11 and 87.97; respectively. The highest metallization rate obtained as % 92.02 at the end of 60. minutes by reducing briquettes which are produced with % 40 mill scale+ % 60 magnetite ore concentrate+ soma-lignite coal mixture. In the reduction experiments show that, mill scale which was ungrinded very fine sizes can be used for produce industrial direct reduced iron. Increasing the amount of oxide layer on the metallization ratio, there was no significant effect.
Research On Usability Of Mill Scale By Mixing With Iron Ore Concentrate In Pellet Production And Reducibility Of This Mixture
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2012
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2012
Keywords: Tufal; Manyetit Cevheri; İndirgeme; Peletleme.; Mill Scale; Magnetite Ore; Reduction; Pelletizing.